The Effectiveness of the Finger Grip Relaxation Technique to Reduce Pain Intensity in Post-Appendectomy Patients: A Literature Review - Calisanie, Nyayu Nina Putri; Ratnasari, Anisa Nur (KnE Life Sciences, 2021)
Appendicitis is an inflammation of the appendix. Post-appendectomy patients often experience pain from the surgical wound incisions. Pain will have an impact on daily activities. Therefore, independent nursing action is needed by performing simple and easy pain management; one methods is finger grip relaxation. To measure the effect of finger relaxation techniques on pain reduction in post-appendectomy patients, this study used a literature review method. The data was collected by searching on Google Scholar website with the following keywords: Finger Grip Relaxation Techniques, Pain, and Appendicitis. It was found that in post-appendectomy surgery patients before being given a finger grip relaxation technique, the patients experienced moderate pain, then after being given a finger grip relaxation technique, the pain intensity decreased and effectively. Data were analysed by Paired T-Test with a significant value α=0.005. The results showed the average result before intervention was 4.80 and the average result after intervention was 3.87. The bivariate results obtained p-value 0,000. It shows that there are differences in pain intensity before and after finger grip relaxation techniques are performed in post-appendectomy patients [3]. It can be concluded that finger grip relaxation techniques can be used as an intervention in the hospital or at home to reduce pain in post-appendectomy patients. Keywords: Finger Grip Relaxation Techniques, Pain, Appendicitis.